All-Ceramic Crown Tooth Preparation and Provisional Crown Fabrication - Cecilia Aragon (Association of American Medical Colleges, 2009)
Abstract This 30-minute instructional video depicts the step-by-step procedures required for the preparation of a maxillary central incisor for an all-ceramic full coverage restoration and the fabrication of a provisional restoration in a mannequin. The recording is divided into two parts. The first part lasts 19 minutes and outlines the 10 sequential steps involved in an all-ceramic tooth preparation. The second part of the video lasts 11 minutes and is divided into four segments depicting the fabrication of the provisional restoration for the prepared tooth. This resource was developed in response to dental student criticism regarding how difficult it is for them to visually appreciate the live demonstrations taught in simulation clinic since the mannequin's oral cavity is small. They had to take sequential turns during these demonstrations in order to be able to get close enough to their instructor while he or she was performing a particular task. As such, it was rare for each student to be able to watch their instructor perform a given procedure from start-to-finish. While having an inadequate field-of-view is an issue for any dental procedure that students are attempting to learn, it can be a particular hindrance in fixed prosthodontics. Therefore, the creation of an instructional aide that will help to alleviate the issue of a lack of visual access is warranted. Over the past few decades, new technology has been introduced into the dental classroom setting, including the use of instructional video and computer-based simulation. Previous studies on these as preclinical teaching aids have reported favorable results both in terms of student attitudes and learning outcomes. Although instructional videos have been developed in dentistry, none of these have involved the demonstration of an all-ceramic tooth preparation and/or provisional crown fabrication.